Song of Songs - Griffiths, Paul J. (Grand Rapids, MI : Brazos Press, 2011)
"The Brazos Theological Commentary on the Bible makes a most welcome contribution to the church, the academic world, and the general public at large. By enlisting a wide range of Protestant, Catholic, and Orthodox theologians who differ on much, but who agree on the truth of the Nicene Creed, the series also represents ecumenical activity of the very best kind. It is always a daunting challenge to expound the church's sacred book both simply and deeply, but this impressive line-up of authors is very well situated for the attempt." -- Mark A. Noll, University of Notre Dame.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries